Review Jurnal: Evaluasi Kekerasan Sediaan Tablet Kunyah dengan Metode Kempa Langsung - Ghina Faiha; Rina Suspa Nita; Nadia Nadia; Devira Niken Putri Ferdinand; Akhmad Rizky Akbar; Nor Latifah (STIKes Ibnu Sina Ajibarang, 2024)
Tablets are one of the most widely used forms of preparation on the market, one type of tablet preparation is chewable tablets. Chewable tablets are drugs that are consumed by chewing first before being swallowed. The manufacture of chewable tablets usually uses the direct felt method which is done by directly shaking a mixture of powder (active substances and excipients). The purpose of this article is to analyze various aspects related to the quality, efficiency, and stability of chewable tablets made using the direct felt method, to identify the hardness test parameters. The method used in this article includes a literature analysis from five journals that discuss the hardness test on chewable tablets on several formulations used. The level of hardness on the tablet was carried out using a hardness tester. Tablets are declared good or meet the requirements when at a weight of 4-8kg the tablets are crushed.